ChoiCo, SorBET, MaLT2: Building Computational Thinking Experiences: Building Computational Thinking Experiences With Digital Authoring Tools in Interdisciplinary Contexts (Constructionism Conference Proceedings, 2025)
This workshop addresses the pressing need to broaden computational thinking (CT) beyond traditional coding exercises by integrating digital authoring tools into diverse, culturally relevant and interdisciplinary activities. In today’s rapidly evolving educational landscape, CT is recognised as a vital 21st-century literacy; yet its implementation has often been confined to isolated programming contexts. The workshop offers a series of hands-on activities rooted in constructionist learning principles and based on recent insights from the fields of embodied cognition, game-based learning, and data science. Utilizing three innovative tools – 1. ChoiCo, which enables the modification of socio-scientific simulation games; 2. SorBET, which supports the design of classification games; and 3. MaLT2, which facilitates the creation of 3D animations that merge artistic expression with mathematical modeling – the workshop aims at bridging theory and practice. It not only demonstrates practical applications of these tools in lesson planning, but also provokes deeper discussion about their underlying theoretical foundations. By outlining concrete strategies for classroom integration, the workshop addresses the needs of diverse learner groups, from novice students to educators seeking innovative instructional techniques. Ultimately, it aims to extend current CT research by exploring its interdisciplinary applications and equipping practitioners with adoptable tools and methodologies, thereby linking CT with data science, mathematical modeling, creative-artistic expression, and critical thinking on socio-scientific, cultural, and ethical issues.